Influence of motivation, library materials and location on use of library by undergraduates in University of Ibadan, Nigeria (2017)
The study investigated the influence of motivation, availability and adequacy of library materials as well as library location on the use of library by undergraduates of University of Ibadan, Nigeria. The convenience sampling technique was adopted to select only 150 undergraduates while a questionnaire was used as the major instrument for data collection. Findings from the study revealed provision of a conducive library environment, ICT facilities, availability of books supporting a student centered curriculum and group reading as major factors which motivate undergraduate students of University of Ibadan towards library use. Textbooks, reference resources, journals, newspapers as well as magazines were found to be the major library materials available to students while adequacy of special collections and government publications, audiovisual materials, electronic resources and students' long essays in meeting the needs of undergraduates of the University of Ibadan was established. Location of the library was found to be adequate and easily accessible to the undergraduates. Positive relationships between motivation, library availability, adequacy, location and use of library were established which implies that proper motivation of undergraduates, high level of availability and adequacy of library materials as well ease of accessing the location of library have positive impact on use of library among the undergraduates of University of Ibadan, Nigeria. The study recommended proper motivation of undergraduates towards library use, provision of relevant library materials in adequate quantity and quality as well as location of the university library where it can be easily accessible to ensure regular use of the library by the undergraduates of the University of Ibadan, Nigeria.